TUMBUHAN PAKAN TERNAK LOKAL DI KABUPATEN PANDEGLANG, BANTEN - Prawiradiputra, Bambang R. (Pastura; Vol 5 No 1 (2015): Pastura Vol. 5 No. 1 Tahun 2015DO - 10.24843/Pastura.2015.v05.i01.p01, 2017)
In 2009 The Indonesian Research Institute for Animal Production in cooperation with The Assessment Institute for Agricultural Technology of Province of Banten and Livestock Service of District of Pandeglang has established the “Kampoeng Ternak” or “Village of Livestock” in the Village of Juhut, Sub-District of Karangtanjung, District of Pandeglang, Province of Banten. Its main activity was to improve sheep breeders including improved its feed. One of the improvements was to identification of the forage commonly given to the sheep. Of some forage found in the sheepfold, there were nine species of plant which was local forage that had never been identified elsewhere before. The nine species were (in local language) kondang (Ficus variegata), beunying (Ficus fustulosa), camun (Pipturus incanus), gedebang (Piper aduncum), hareunga (Gynura aurantica), kareumbi (Homalanthus populnea), ki tongo (Debregeasia longifolia), leles and nangsi (Villebrunea rubescens). In addition it was also found gamal (Gliricidia maculata), kaliandra (Calliandra calothyrsus), jengjen (Falcataria sp.), mani’i (Miopsis sp.), mindi (Melia azedarach), dadap (Erythrina lithosperma) and nangka or jackfruit (Artocarpus integra). In this paper discussed in brief taxonomy, morphological characteristics and ecology of the forage plants. Keywords: local forage, dry land, sheep